Hubungan gangguan pendengaran dengan kualitas hidup pada lansia - Suharti, Sri; Wulan, Sarinah Sri (THE JOURNAL OF Nursing Management Issues, 2024)
Background: Hearing loss is a common health problem among older adults. Hearing loss can lead to social isolation, depression, and withdrawal from life activities, which can impact quality of life. The four domains of quality of life are defined as subjective perception or experience, behavior, potential capacity, and state of being. Purpose: To determine the relationship between hearing impairment and quality of life in the elderly at the UPTD PSLU Tresna Werdha Natar, South Lampung. Results: Quality of life was good as many as 14 respondents (58.3%), and 10 respondents (41.7%). From the correlation test, it was found that the p-value was 0.050 (0.05), which means that there is a tendency that the elderly with hearing loss have a poor quality of life. Method: Quantitative research using cross-sectional design with 24 elderly respondents using purposive sampling technique, data collection tool using a questionnaire in the form of a favorable scale of 1-5, this research variable uses two variables. Results: Fourteen respondents (58.3%) reported good quality of life, while 10 respondents (41.7%) reported poor quality of life. The correlation test yielded a p-value of 0.050 (0.05), indicating a tendency for elderly people with hearing impairment to have a poorer quality of life. Conclusion: There is a relationship between hearing impairment and quality of life in elderly people at the UPTD PSLU Tresna Werdha Natar, South Lampung.   Keywords: Elderly; Hearing Loss; Quality of Life.   Pendahuluan: Gangguan pendengaran adalah salah satu masalah kesehatan yang umum dijumpai pada lansia. Hilangnya pendengaran dapat menyebabkan terjadinya isolasi sosial, depresi dan menarik diri dari aktivitas hidup yang dapat mempengaruhi kualitas hidup. Empat domain kualitas hidup diartikan sebaga isuatu persepsi  atau pengalaman subjektif, perilaku, kapasitas potensial dan status keberadaan. Tujuan: Untuk mengetahui hubungan gangguan pendengaran dan kualitas hidup pada lansia di UPTD PSLU Tresna Werdha Natar Lampung Selatan. Metode: Penelitian kuantitatif desain crosssectional dengan jumlah responden 24 lansia dengan teknik sampel teknikpurposive sampling, alat pengambilan data dengan kuesioner berbentuk favorable dengan skala 1-5, variable penelitian ini menggunakan dua variable. Hasil: Kualitas hidup baik sebanyak 14 responden (58,3%), dan pengetahuan hidup buruk sebanyak 10 responden (41,7%). Dari uji korelasi didapatkan nilai p-value 0,050 (0,05), yang artinya terdapat kecenderungan bahwa lansia yang memiliki gangguan pendengaran memiliki kualitas hidup yang kurang baik. Simpulan: Terdapat hubungan antara gangguan pendengaran dan kualitas hidup pada lansia di UPTD PSLU Tresna Werdha Natar Lampung Selatan.   Kata Kunci: Gangguan Pendengaran; Kualitas Hidup; Lansia.